2022
DOI: 10.7150/ntno.73918
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Applying Carbon Dots for Inhibition of RNA Virus Infection

Abstract: Viral infection is a globally leading health issue. Annually, new lethal RNA viruses unexpectedly emerged and mutated threatening health and safety. Meanwhile, it is urgent to explore novel antiviral agents, which, however, takes years to be clinically available. Nonetheless, the development of carbon dots (CDs) in the past 20 years has exhibited their vast application potentials and revealed their promising capacity as future antiviral agents considering their versatile properties and significant antiviral re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…The pyrolysis of curcumin yielded these hydrophilic, positively charged, 1.5 nmsized antiviral fluorescent CCM-C-dots that are very effective against coronavirus models (porcine epidemic diarrhea virus). 93 In 2020, Tong et al found that respiratory syndrome virus (PRRSV) is suppressed by Gly-C-dots produced from glycyrrhizic acid and observed that Gly-C-dots possess a high level of antiviral activity on this specific virus. In conclusion, it was dictated that Gly-C-dot is not an effective preventer of either adsorption or release of PRRSV progeny when effects on viral proliferation were studied, focusing on stages of adsorption, invasion, replication, and release.…”
Section: ■ Methods Of Synthesis Of C-dotsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pyrolysis of curcumin yielded these hydrophilic, positively charged, 1.5 nmsized antiviral fluorescent CCM-C-dots that are very effective against coronavirus models (porcine epidemic diarrhea virus). 93 In 2020, Tong et al found that respiratory syndrome virus (PRRSV) is suppressed by Gly-C-dots produced from glycyrrhizic acid and observed that Gly-C-dots possess a high level of antiviral activity on this specific virus. In conclusion, it was dictated that Gly-C-dot is not an effective preventer of either adsorption or release of PRRSV progeny when effects on viral proliferation were studied, focusing on stages of adsorption, invasion, replication, and release.…”
Section: ■ Methods Of Synthesis Of C-dotsmentioning
confidence: 99%
“…C-dots have demonstrated their ability to be inhibitors on a multisite level against the enteric coronavirus. The pyrolysis of curcumin yielded these hydrophilic, positively charged, 1.5 nm-sized antiviral fluorescent CCM-C-dots that are very effective against coronavirus models (porcine epidemic diarrhea virus) …”
Section: Biological Activity Of C-dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, discussing the methods of carbon dots synthesis is as important as discussing their applications. Under this circumstance, several studies reported synthetic methods of carbon dots [32][33][34][35][36][37]. Therefore, synthesis methods of carbon dots would not be discussed immensely.…”
Section: Advances In Carbon Dots Synthesismentioning
confidence: 99%
“…Once CDs enter the brain, CDs incorporating contrast agents enable magnetic resonance imaging (MRI). In addition, certain CD species were observed to target bones and inhibit both the replication and cell entry of viruses such as human immunodeficiency virus (HIV) and SARS-CoV-2 . Most significantly, the singlet oxygen and ROS generated in the aforementioned photocatalysis have promoted the applications of CDs in photodynamic therapies, which are often accompanied by photothermal therapies. , Compared to the other areas, studies on the surface chemistry of CDs are insufficient.…”
Section: Introductionmentioning
confidence: 99%